THE INFLUENCE OF DRUG INFORMATION ON DRUG SELECTION AND USAGE COUGH PREPARATION AT SELF MEDICATION IN GODEAN SUBDISTRICT - ., Satibi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
The influence of drug information on drug selection and usage cough preparation for self medication in Godean was investigated. The study was performed in Godean community by distributing questioner to respondences. Stratified random sampling followed by equal sampling were used to select subjects. Multiple regression and t-test were used to analyzed the result statistically. The result showed that drug information influences drug selection and usage (Z1/2ï¡ = 0,050). Key words : Self medication, information, cough medicine